1985
DOI: 10.1021/bi00348a034
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of lipid binding and kinetic properties of normal, variant, and .gamma.-carboxyglutamic acid modified human factor IX and factor IXa

Abstract: The abilities of normal and three abnormal factor IXa molecules to activate factor X and to bind to phospholipid membranes have been compared to define the contributions of protein-lipid interactions and factor IXa light chain-heavy chain interactions to the functioning of this protein. The abnormal proteins studied had altered amino acid residues in their light chains. The heavy-chain regions, containing the active site serine and histidine residues, were normal in the abnormal proteins on the basis of titrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

1988
1988
2002
2002

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 30 publications
2
11
0
Order By: Relevance
“…This study shows that factor VIIa binds to platelets with a K d of about 100 nM. This value is similar to the affinity of factor IXa for phospholipid vesicles (Jones et al, 1985) and low-affinity factor IXa binding to platelets (Hoffman et al, 1992a) but is tighter than previously observed for factor VIIa binding to phospholipid vesicles (Bom & Bertina, 1990). Hedner et al (1993), using a modified coagulation assay described by Lindley et al (1994), showed that individuals Factor X activation on platelets in the presence of factor VIIa.…”
Section: Discussionsupporting
confidence: 77%
“…This study shows that factor VIIa binds to platelets with a K d of about 100 nM. This value is similar to the affinity of factor IXa for phospholipid vesicles (Jones et al, 1985) and low-affinity factor IXa binding to platelets (Hoffman et al, 1992a) but is tighter than previously observed for factor VIIa binding to phospholipid vesicles (Bom & Bertina, 1990). Hedner et al (1993), using a modified coagulation assay described by Lindley et al (1994), showed that individuals Factor X activation on platelets in the presence of factor VIIa.…”
Section: Discussionsupporting
confidence: 77%
“…The interaction of this factor IX with phospholipids was normal, but the activation of factor X either in the presence or absence of factor VIII was found to occur at a reduced rate, relative to the normal protein (Briet et al, 1982;Jones et al, 1985). The level of (3-hydroxyaspartate was found to be normal in this variant (McGraw et al, 1985).…”
Section: Discussionmentioning
confidence: 95%
“…The rest of the cascade follows the intrinsic pathway including the formation of a factor IXa–factor VIIIa complex, activation of factor X and then generation of thrombin. In these reactions, the presence of phospholipid is also essential (Jones et al , 1985; Liebman et al , 1987). Either phopholipid vesicle or cell surface is required for the enzymatic activity of factor IXa (Van Dieigen et al , 1981).…”
Section: Discussionmentioning
confidence: 99%